Analisis Kesalahan Berpikir Pseudo dalam Memecahkan Masalah Matematis Ditinjau dari Self Confidence - Salsabila; Ervin Azhar (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to explain students pseudo-thinking errors on mathematical problem-solving skills that are reviewed supported on high, medium, and low self-confidence. This research was conducted at SMAN 60 Jakarta class XI MIPA II for the 2020/2021 academic year. The subjects taken were 3 out of 38 students. This research method is a descriptive qualitative approach. Researchers used self-confidence questionnaires, problem-solving ability tests, and interviews. The material being tested is the derivative of algebraic functions. The results obtained stated that students with high self-confidence scored perfect test scores but there were a few writing errors. The completion step, therefore, included pseudo-correct thinking. Students with moderate self-confidence can do the questions well, but there are inaccuracies so that the results are wrong. Therefore, students with moderate self-confidence enter the indicator of pseudo-wrong thinking errors with information that can reflect on their answers. In students with low self-confidence, they face errors in compiling the completion steps but can rectify and find the correct answer. With this, students with low self-confidence fall into the indicator of pseudo-correct thinking errors with information on understanding the wrong concept.